Molecular Monitoring of Plasmodium vivax Infection afterRadical Treatment in Southeastern Iran - M Nateghpour; S Ayazian Mavi; H Keshavarz; S Rezaei; F Abedi; Gh Edrissian; R Raeisi (Tehran University of Medical Sciences, 2010)
Background: The aim was to evaluate the relapse risk of vivax malaria in patients who received radical treatment in Hormozgan Province, a malarious area located on southeast of Iran. Methods: A total of 95 symptomatic vivax malaria infected patients were enrolled in urban health centers of Bandar- Abbas, Minab, Bandar-Jask and Bashagard districts of Hormozgan Province, southeast of Iran from January 2008 to March 2009 for consideration as a case- series study. DNA was extracted from parasite infected whole blood samples. A polymorphic region of Plasmodium vivax merozoite surface protein 1 (pvMSP1) was selected and a PCR method was employed for all the samples to amplify the specific variable gene fragment. The obtained fragments in primary and secondary samples were sequenced. Both nucleotide and amino acid sequences of the samples were investigated for returned patients. Results: 3.2% of the patients experienced a second attack between 83-199 days after the initial episode of infection. Alignment of nucleotide and their deduced amino acid sequences between pair sequences of primary and secondary isolates revealed 8 and 6 dissimilarities respectively for the first case, and 9 and 7 dissimilarities for the second case. Although microscopical examination of recurrent thick blood smear of the third patient confirmed new P. vivax  infection, the venous blood sample was accidentally missed. Sequencing results of primary and returned isolates 1P, 1S, 2P, 2S and 3P in this study showed an identity with BP13, T117, BP13, TC28 and Chesson genotypes respectively. Conclusion: The returned (secondary) isolates may account to be for the sake of reinfection.